Heal The World Song Lyrics by Michael Jackson: Syntactic and Semantic Study - Heri Hidayat; Ervina C M Simatupang (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
This study explores the syntactic and semantic dimensions of the iconic song lyrics,